2019
DOI: 10.1021/acs.energyfuels.9b01264
|View full text |Cite
|
Sign up to set email alerts
|

Energy Conversion Efficiency of Pyrolysis of Chicken Litter and Rice Husk Biomass

Abstract: Pyrolysis is a well-established method of converting biomass to different types of value-added products, such as high energy density biofuels and chemicals. In this work, chicken-litter waste and rice husk were pyrolyzed at different temperatures with the aim of investigating the thermal behavior and energy recovery potential of the feedstocks. Computer-aided thermal analysis and thermogravimetric analysis were employed to study the pyrolysis properties of each biomass in a temperature-controlled regime. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…On the other hand, it is noteworthy that the energy required to heat the biomass to the operating temperature of pyrolysis (i.e., 500 °C) and for biomass pyrolysis reaction are around 0.98 MJ kg −1 and 1.01 MJ kg −1 respectively. Similar results have been reported in Yang et al (2013) and Weldekidan et al (2019), where they estimated the heat required for biomass pyrolysis by using TGA-DSC experiment. Their results concluded that the energy demand for heating the rice husk and chicken litter to the pyrolysis temperature of 500 °C were 0.8 MJ kg −1 and 1.2 MJ kg −1 respectively, while the heat energy consumed for pyrolysis process of five different biomass samples was in the range of 1.1-1.6 MJ kg −1 at pyrolysis temperature between 500 and 550 °C.…”
Section: A Base Case Study Of the Biomass Pyrolysis-solid Oxide Fuel ...supporting
confidence: 85%
“…On the other hand, it is noteworthy that the energy required to heat the biomass to the operating temperature of pyrolysis (i.e., 500 °C) and for biomass pyrolysis reaction are around 0.98 MJ kg −1 and 1.01 MJ kg −1 respectively. Similar results have been reported in Yang et al (2013) and Weldekidan et al (2019), where they estimated the heat required for biomass pyrolysis by using TGA-DSC experiment. Their results concluded that the energy demand for heating the rice husk and chicken litter to the pyrolysis temperature of 500 °C were 0.8 MJ kg −1 and 1.2 MJ kg −1 respectively, while the heat energy consumed for pyrolysis process of five different biomass samples was in the range of 1.1-1.6 MJ kg −1 at pyrolysis temperature between 500 and 550 °C.…”
Section: A Base Case Study Of the Biomass Pyrolysis-solid Oxide Fuel ...supporting
confidence: 85%
“…In general, over 70% of the municipal waste plastic was converted into oil at each trial of the process with the entire pyrolytic system having an average overall conversion efficiency of 96.67%. Similar efficiency results were achieved by Weldekidan et al (2019) using chicken litter and rice husk as feed.…”
Section: Conversion Efficiencysupporting
confidence: 79%
“…Pyrolysis efficiency is the thermal efficiency obtained as the ratio of the difference between the overall heating values of the pyrolytic products and the total thermal energy utilized for processing the sample. Pyrolysis is a well-known process of producing high energy-density biofuels and chemicals [24]. Wang et al [25] presented a comprehensive overview of the pyrolysis mechanisms of three biopolymers in biomass materials and highlighted the complexities in their structure.…”
mentioning
confidence: 99%